Impact of the COVID-19 Pandemic on the Mental Health and Quality of Life of Patients with Psoriasis in Tertiary Care; A One-year Follow-up - Georgia Lada; Hector Chinoy; Peter S. Talbot; Richard B. Warren; C. Elise Kleyn (Medical Journals Sweden, 2022)
Abstract is missing (Short communication)